Immune Modulation as Adjunctive Therapy for Pneumocystis pneumonia - Jing Wang; Terry W. Wright; Francis Gigliotti (Interdisciplinary Perspectives on Infectious Diseases)
Pneumocystis is an opportunistic fungal respiratory pathogen that causes life-threatening pneumonia (Pcp) in patients suffering from defects in cell-mediated immunity, including those with acquired immunodeficiency syndrome (AIDS) and immunosuppression secondary to chemotherapy or organ transplantation. Despite major advances in health care, the mortality associated with Pcp has changed little over the past 25  years. Pcp remains a leading cause of death among HIV infected patients, with mortality rates of 50% or higher for patients developing severe Pcp. In addition, as more potent immunosuppressive therapies are developed for chronic inflammatory diseases, more cases of Pcp are occurring in non-HIV patients and in previously unreported clinical settings. These features highlight the importance of developing a better understanding of the pathogenesis of this disease, and the need to search for new therapeutic strategies to improve the outcome of Pcp patients. Immune-mediated inflammatory responses play an important role in the pathogenesis of Pcp, and may be even more significant in determining the outcome of Pcp than direct damage due to the organism itself. In this review we will summarize the immunopathogenic mechanisms that contribute to Pcp-associated lung injury, and discuss the potential to target these pathways for adjunctive immune modulation therapy for Pcp.